If f(x) = 3x^2 -4 and g(x) = 2x -1, what is (f of g)(x)?

### 2 Answers | Add Yours

(f of g)(x)=f(g(x))

`f(g(x))=3(2x-1)^2-4`

`=3(4x^2-4x+1)-4`

`=12x^2-12x+3-1`

`=12x^2-12x+2`

**Sources:**

### 1 Reply | Hide Replies ▲

`12z^2-12x+3-4`

`12x^2-12x-1`

We have given

`f(x)=3x^2-4 ` and `g(x)=2x-1` ,We wish to find `fog(x)`

`fog(x)=f(g(x))`

`=f(2x-1)=3(2x-1)^2-4`

`=3(4x^2-4x+1)-4`

`=12x^2-12x+3-4`

`=12x^2-12x-1`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes